The Safety and Efficacy of Varenicline in Cocaine Using Smokers Maintained on Methadone: A Pilot Study - Poling, James (2010)
In this double-blind, placebo-controlled trial, we compared varenicline (2 mg) to placebo for treatment for cocaine and tobacco dependence in 31 methadone-maintained subjects. Subjects received weekly counseling during the 12-week study participation. Our results indicate that varenicline is safe to give to this subject population, as there were no adverse events related to medication during this study. Varenicline was no more effective than placebo for abstinence from cocaine. Treatment with varenicline was associated with a reduced number of cigarettes smoked per day, even though subjects received only a brief education for smoking cessation. The self-report reduction in smoking was corroborated by CO levels and the Fagerström Test of Nicotine Dependence. However, self-ratings of positive mood on the Positive Affect Negative Affect Schedule did significantly decrease in the varenicline group as compared to the placebo group, although this appears to be due to randomization differences related to lifetime depression diagnosis. These preliminary findings may point to potential therapeutic value of varenicline for smoking cessation in cocaine users maintained on methadone.